CREATIVE PACKAGING SEBAGAI UPAYA PENINGKATAN DAYA SAING PRODUK KULINER “SERUNDENG” SEBAGAI OLEH-OLEH KHAS BALI - Ni Nyoman Adityarini Abiyoga Vena Swara; Ni Luh Adisti Abiyoga Wulandari; Mirah Ayu Trarintya; I Wayan Budi Satriya; Ida Bagus Gede Parandita; Ni Kadek Sintha Rila Cahyani (JURNAL SEWAKA BHAKTI, 2023)
The emergence of Balinese Culinary MSMEs indicates that this business is very promising. One of them is the UMKM "Serundeng Bali" in Pesaban Village, Rendang District, Karangasem Regency. Mrs. Nyoman Ambih Hartini as a partner entrepreneur has been running this business for three years by utilizing the results of coconut plantations. So far, the abundant coconut plantation products besides being sold in the form of whole coconuts, are partly processed into a product of serundeng which has been used for family consumption and ceremonial needs as well as partly being traded to traditional markets around the business location. Product marketing is still limited because it does not have special packaging so there are no modern marketing efforts such as the use of social media and e-commerce. The product is also not equipped with a product label as the identity of the brand name and manufacturer. In addition, partner entrepreneurs do not yet have financial records, so they do not know the profit/loss of the business they have been running. Based on the analysis of the situation in the "Serundeng Bali" MSME, assistance is provided for the creation of creative packaging and product labels as an effort to increase product competitiveness so as to expand market and marketing. Through this assistance, it is hoped that partner entrepreneurs and employees will have the ability to innovate products through making attractive packaging and that MSMEs have a corporate identity in the form of product labels. In addition, assistance is provided for the use of social media and e-commerce as promotional media to strengthen branding and marketing activities for serundeng products as traditional culinary souvenirs typical of Bali.